مقارنة طرائق تقدير معلمات دالة الشدة لعمليات بواسون غير المتجانسةمقارنة طرائق تقدير معلمات دالة الشدة لعمليات بواسون غير المتجانسةمقارنة طرائق تقدير معلمات دالة الشدة لعمليات بواسون غير المتجانسة - عباس, خالد ضاري; لازم, جاسم حسن (Journal of Economics and Administrative Sciences, 2010)
This research deals with parameters estimation methods for the intensity function of non homogeneous poisson processes , it aims to estimate parameters of this function throughout three methods which are maximum likelihood method , moment method and shurnkage method using simulation method.In order to achive the best method, several assumed values for parameters of intensity function have been adopted  using sample size of  (14, 25, 50, 100) .Results of estimation showed that the estimation over the estimation method , of maximum likelihood and moment .  This estimation gain the least mean of squares error for the above samples .